2023
DOI: 10.3390/nu15051194
|View full text |Cite
|
Sign up to set email alerts
|

“I Always Buy the Purple Ones … If I See Them”: Socioecological Factors Influencing Anthocyanin-Rich Food Consumption for Cognitive Health in Older Adults

Abstract: Despite the positive relationship between anthocyanin-rich foods and cognitive health, a dietary deficit exists in older adults. Effective interventions require an understanding of people’s dietary behaviors situated in social and cultural contexts. Therefore, the aim of this study was to explore older adults’ perceptions about increasing their consumption of anthocyanin-rich foods for cognitive health. Following an educational session and the provision of a recipe and information book, an online survey and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Color and appearance are the characteristics that influence the behavior of Romanian respondents as consumers [87]. However, the respondents who lived and still live in the rural environment, according to the results of our study, remain encouraged in the patterns of traditional food behavior, as indicated in the study) [55,[88][89][90][91][92][93][94].Traditional products do not meet their expectation, which leads them to resort to re-purchasing the products and/or directing others to them purchase. The results from the sensory evaluation correlate with the label (ST7), which confirms that traditional food fits this type of consumer.…”
Section: Results On Consumer Surveymentioning
confidence: 66%
“…Color and appearance are the characteristics that influence the behavior of Romanian respondents as consumers [87]. However, the respondents who lived and still live in the rural environment, according to the results of our study, remain encouraged in the patterns of traditional food behavior, as indicated in the study) [55,[88][89][90][91][92][93][94].Traditional products do not meet their expectation, which leads them to resort to re-purchasing the products and/or directing others to them purchase. The results from the sensory evaluation correlate with the label (ST7), which confirms that traditional food fits this type of consumer.…”
Section: Results On Consumer Surveymentioning
confidence: 66%